Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.ijrobp.2013.06.950
|View full text |Cite
|
Sign up to set email alerts
|

The Non-Gaussian Nature of Prostate Motion Based on Real-Time Intrafraction Tracking

Abstract: Purpose-The objective of this work is to test the validity of the Gaussian approximation for prostate motion through characterization of its spatial distribution.Methods and Materials-Real-time intrafraction prostate motion was observed using Calypso 4-dimensional (4D) nonradioactive electromagnetic tracking system. We report the results from a total of 1024 fractions from 31 prostate cancer patients. First, the correlation of prostate motion in right/left (RL), anteroposterior (AP), and superoinferior (SI) di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…For that purpose, wavelet decomposition is used in our study because it is ideal for situations where a repetitive pattern caused by respiration exists amidst background noise caused by prostate drifting and bladder or rectal filling. We have shown in our previous publication (12) that the prostate motion in the AP/SI direction is highly correlated, which is consistent with the longitudinal oblique motion of the prostate, and likely due to the effect of respiration on an organ confined between the bladder and rectum. For this reason, the magnitude and peak frequency of the respiratory motion are extracted from the displacement in the oblique direction ( y2+z2) (y-axis for AP and z-axis for SI).…”
Section: Resultssupporting
confidence: 86%
“…For that purpose, wavelet decomposition is used in our study because it is ideal for situations where a repetitive pattern caused by respiration exists amidst background noise caused by prostate drifting and bladder or rectal filling. We have shown in our previous publication (12) that the prostate motion in the AP/SI direction is highly correlated, which is consistent with the longitudinal oblique motion of the prostate, and likely due to the effect of respiration on an organ confined between the bladder and rectum. For this reason, the magnitude and peak frequency of the respiratory motion are extracted from the displacement in the oblique direction ( y2+z2) (y-axis for AP and z-axis for SI).…”
Section: Resultssupporting
confidence: 86%
“…The first contributing factor has been widely investigated in the literature and the results are generally in agreement, pointing out a global motion towards the posterior and caudal directions and a much less notable lateral component of motion. These findings are consistent with the theory that the morphologic modifications of bladder and rectum affect prostate position, thus determining the main direction of the observed motion (15-16-17).…”
Section: Introductionsupporting
confidence: 90%
“…The global motion of the prostate during RT treatments has been extensively investigated with different techniques by several groups (13,(15)(16)(17)(25)(26)(27). However, few studies focused on the analysis of the intrafraction BIPM (18)(19)(20)(21)23).…”
Section: Discussionmentioning
confidence: 99%
“…Several independent studies, using different methods, have found similar prostate motion trajectories. There are six different prostate motion patterns described [9][10][11][12][13]. The pattern of an individual patient is unpredictable and any of the six motion patterns can occur during each fraction.…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of an individual patient is unpredictable and any of the six motion patterns can occur during each fraction. In any case, the positional uncertainty increases with time [12][13][14][15][16]. The increased dose per fraction and thereby increased treatment time for hypofractionation could lead to larger positional uncertainty due to the prostate motion.…”
Section: Introductionmentioning
confidence: 99%